Pharmacological and neurosurgical interventions for managing dystonia in cerebral palsy: a systematic review. (6th February 2018) - Fehlings, Darcy; Brown, Leah; Harvey, Adrienne; Himmelmann, Kate; Lin, Jean‐Pierre; Macintosh, Alexander; Mink, Jonathan W; Monbaliu, Elegast; Rice, James; Silver, Jessica; Switzer, Lauren; Walters, Ilana
Abstract : Aim: To systematically review evidence for pharmacological/neurosurgical interventions for managing dystonia in individuals with cerebral palsy (CP) to inform a care pathway. Method: Searches included studies with a minimum of five participants with dystonia in CP receiving oral baclofen, benzodiazepines (clonazepam, diazepam, lorazepam), clonidine, gabapentin, levodopa, trihexyphenidyl, botulinum toxin, intrathecal baclofen (ITB), or deep brain stimulation (DBS). Evidence was classified according to American Academy of Neurology guidelines. Results: Twenty‐eight articles underwent data extraction: one levodopa, five trihexyphenidyl, three botulinum toxin, six ITB, and 13 DBS studies. No articles for oral baclofen, benzodiazepines, clonidine, or gabapentin met the inclusion criteria. Evidence for reducing dystonia was level C (possibly effective) for ITB and DBS; level C (possibly ineffective) for trihexyphenidyl; and level U (inadequate data) for botulinum toxin. Interpretation: For dystonia reduction, ITB and DBS are possibly effective, whereas trihexyphenidyl was possibly ineffective. There is insufficient evidence to support oral medications or botulinum toxin to reduce dystonia. There is insufficient evidence for pharmacological and neurosurgical interventions to improve motor function, decrease pain, and ease caregiving. The majority of the pharmacological and neurosurgical management of dystonia in CP is based on clinical expert opinion. What this paper adds: Intrathecal baclofen and deep brain stimulation are possibly effective in reducing dystonia. Current evidence does not support effectiveness of oral medications or botulinum toxin to reduce dystonia. Evidence is inadequate for pharmacological/neurosurgical interventions impact on improving motor function, pain/comfort, and easing caregiving. The majority of the care pathway rests on expert opinion. What this paper adds: Intrathecal baclofen and deep brain stimulation are possibly effective in reducing dystonia. Current evidence does not support effectiveness of oral medications or botulinum toxin to reduce dystonia. Evidence is inadequate for pharmacological/neurosurgical interventions impact on improving motor function, pain/comfort, and easing caregiving. The majority of the care pathway rests on expert opinion. This article is commented on by Carr on pages331–332 of this issue. This article's abstract has been translated into Spanish and Portuguese. Follow the links from theabstract to view the translations. Video Podcast:https://www.youtube.com/watch?v=MwpWGfssCII&feature=youtu.be